Effects of Naringin on Proliferation and Osteogenic Differentiation of Human Periodontal Ligament Stem Cells In Vitro and In Vivo - Lihua Yin; Wenxiao Cheng; Zishun Qin; Hongdou Yu; Zhanhai Yu; Mei Zhong; Kemo Sun; Wei Zhang (Stem Cells International)
This study is to explore the osteogenesis potential of the human periodontal ligament stem cells (hPDLSCs) induced by naringin in vitro and in vitro. The results confirmed that 1 μM naringin performs the best effect and a collection of bone-related genes (RUNX2, COL1A2, OPN, and OCN) had significantly higher expression levels compared to the control group. Furthermore, a typical trabecular structure was observed in vivo, surrounded by a large amount of osteoblasts. These results demonstrated that naringin, at a concentration of 1 μM, can efficiently promote the proliferation and differentiation of hPDLSCs both in vitro and in vivo.